2022
DOI: 10.3390/antiox11030561
|View full text |Cite
|
Sign up to set email alerts
|

Thiol Reductases in Deinococcus Bacteria and Roles in Stress Tolerance

Abstract: Deinococcus species possess remarkable tolerance to extreme environmental conditions that generate oxidative damage to macromolecules. Among enzymes fulfilling key functions in metabolism regulation and stress responses, thiol reductases (TRs) harbour catalytic cysteines modulating the redox status of Cys and Met in partner proteins. We present here a detailed description of Deinococcus TRs regarding gene occurrence, sequence features, and physiological functions that remain poorly characterised in this genus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 180 publications
0
1
0
Order By: Relevance
“…The exact function of this gene is still elusive in D . radiodurans [ 126 ], although irradiation is reported to have induced its expression [ 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…The exact function of this gene is still elusive in D . radiodurans [ 126 ], although irradiation is reported to have induced its expression [ 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…While DNA is not protected from damage, it has been shown that proteins in radiation-resistant organisms are much better protected against oxidative damage than in radiation-sensitive organisms (Daly et al 2007). Deinococcus bacteria are well equipped with enzymatic and non-enzymatic antioxidant systems (Slade and Radman 2011;Daly 2012;Lim et al 2019;de Groot et al 2022). Identified non-enzymatic antioxidant systems and compounds are a high intracellular Mn 2+ /Fe 2+ ratio (limiting Fe 2+ -catalyzed oxidative damage to proteins), small-molecule Mn 2+ -antioxidant complexes, small peptides, carotenoids, and the low-molecular-weight thiol bacillithiol (Daly et al 2004(Daly et al , 2010Tian and Hua 2010;Berlett and Levine 2014;Jeong et al 2021a).…”
Section: Oxidative Stress Defensementioning
confidence: 99%
“…Identified non-enzymatic antioxidant systems and compounds are a high intracellular Mn 2+ /Fe 2+ ratio (limiting Fe 2+ -catalyzed oxidative damage to proteins), small-molecule Mn 2+ -antioxidant complexes, small peptides, carotenoids, and the low-molecular-weight thiol bacillithiol (Daly et al 2004(Daly et al , 2010Tian and Hua 2010;Berlett and Levine 2014;Jeong et al 2021a). Antioxidant enzymes are also important for survival of Deinococcus when exposed to radiation (acute or chronic), desiccation, or oxidants (Lim et al 2019;de Groot et al 2022;Gaidamakova et al 2022;Han et al 2022) (and references therein). These enzymes are for example involved in ROS removal (e.g., superoxide dismutase, catalase, and peroxiredoxin), and protection and repair of oxidation-sensitive cysteine and methionine residues in proteins (thiol reductases).…”
Section: Oxidative Stress Defensementioning
confidence: 99%
See 1 more Smart Citation
“…A couple of Deinococcus strains are relatively well studied for their physiological protective mechanisms under oxidative stress. Various types of protective mechanisms have been described, including (1) pigment-dependent protection with carotenoids, (2) enzymatic defense mechanisms with catalase, peroxidase and superoxide dismutase, (3) metal-ion-dependent protection with the regulation of the iron/manganese ratio, ( 4) examples of well-known stress response regulators including the general antioxidative activator OxyR, superoxide response protein SoxRS, and the alternative sigma factor RpoS, and (5) the regulation of intracellular redox potential by thiol concentrations via cystine import and biosynthesis [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%